Rogue justice ebook - Abrams, Stacey (Avery Keene, 2023)
NEW YORK TIMES BESTSELLER • The #1 bestselling author of While Justice Sleeps returns with another riveting and intricately plotted thriller, in which a blackmailed federal judge, a secret court and a brazen murder may lead to an unprecedented national crisis. "Abrams delivers another smart, zippy thriller." —Washington Post "A thoroughly compelling take on the machinations of Washington and those covetous of power." — New York Magazine Supreme Court clerk Avery Keene is back, trying to get her feet on solid ground after unraveling an international conspiracy in While Justice Sleeps . But as the sparks of Congressional hearings and political skirmishes swirl around her, Avery is approached at a legal conference by Preston Davies, an unassuming young man and fellow law clerk to a federal judge in Idaho. Davies believes his boss, Judge Francesca Whitner, was being blackmailed in the days before she died. Desperate to understand what happened, he gives Avery a file, a burner phone, and a fearful warning that there are highly dangerous people involved.  Another shocking murder leads Avery to a list of names – all federal judges – and, alarmingly, all judges on the FISA Court (the United States Foreign Intelligence Surveillance Court), also known as America’s "secret court." It is this body which grants permission to the government to wiretap Americans or spy on corporations suspected of terrorism. As Avery digs deeper, she begins to see a frightening pattern – and she worries that something far more sinister may be unfolding inside the nation’s third branch of government. With lives at stake, Avery must race the clock and an unexpected enemy to find the answer. Drawn from today’s headlines and woven with her unique insider perspective, Stacey Abrams combines twisting plotlines, wry wit, and clever puzzles to create another immensely entertaining suspense novel.